1978
DOI: 10.1099/0022-1317-41-3-599
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Avirulent Semliki Forest Virus Infections in Athymic Nude Mice

Abstract: SUMMARYThe course and outcome of intraperitoneally induced infections with the avirulent strain A7(74 ) of Semliki Forest virus have been studied in athymic 'nude' (nu/nu) mice, their heterozygous (nu/+) littermates and conventional Swiss A2G mice. The main distinguishing characteristics of the infection in the nu/nu mice were the persistence of virus in the brain after an initial phase of incomplete virus clearance and the apparent establishment of a secondary phase of virus replication in the brain which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 16 publications
0
21
1
Order By: Relevance
“…We did not analyze the tissues beyond 1 week p.i., but it is likely that the virus is cleared and becomes undetectable by immunohistochemistry at later time points. Namely, other groups have reported a transient decline in CNS virus titers in infected nude mice, 22,24 although viral RNA could still be detected by in situ hybridization. The decline in virus antigen observed in the present study correlates with peaking of virus-specific IgM and the leakiness of the bloodbrain-barrier that occurs during infection with avirulent SFV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not analyze the tissues beyond 1 week p.i., but it is likely that the virus is cleared and becomes undetectable by immunohistochemistry at later time points. Namely, other groups have reported a transient decline in CNS virus titers in infected nude mice, 22,24 although viral RNA could still be detected by in situ hybridization. The decline in virus antigen observed in the present study correlates with peaking of virus-specific IgM and the leakiness of the bloodbrain-barrier that occurs during infection with avirulent SFV.…”
Section: Discussionmentioning
confidence: 99%
“…Although not analyzed in the present study, the A7(74) CNS titers have been shown to be restricted also in nude and SCID mice (several magnitudes lower than in WT SFV), indicating that the restriction of A7(74) replication is not mediated by cells of the adaptive immune system. 22,24 The efficacy of the virotherapy in the nude mouse model is demonstrated in Figure 1. However, as opposed to the SCID mouse tumor model data in our previous study, 15 only the intratumoral administration route was effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protected mice (169 in total) were observed for up to 9 months after infection and all but one remained clinically normal. The only other reports of persistent infections with SFV in vertebrate hosts were obtained when the immunological status of the animal had been altered either by prior passive immunization (Seamer et al, 1971) or by using athymic nude mice (Jagelman et al, 1978;Bradish et al, 1979). However, as the persistent infections which we have found were established in immunologically normal mice we conclude that they result directly from the inoculation of DI virus.…”
Section: Persistence Of Virulent Semliki Forest Virus In Mouse Brain mentioning
confidence: 49%
“…(athymic nude mice: Jagelman et al, 1978;Bradish et al, 1979) or has undergone passive immunotherapy (Seamer et al, 1971). Thus, SFV provides a system to test for the possible effects of DI virus on the establishment of persistence in vivo.…”
Section: Persistence Of Virulent Semliki Forest Virus In Mouse Brain mentioning
confidence: 99%